Intrinsic multiferroics in an individual single-crystalline Bi5Fe0.9Co0.1Ti3O15 nanoplate. Issue 40 (5th October 2017) - Chen, Tong; Meng, Dechao; Li, Zhiang; Chen, Jifang; Lei, Zhiwei; Ge, Wen; Sun, Shujie; Sun, Dejuan; Liu, Min; Lu, Yalin
Abstract : Multiferroics Bi5 Fe0.9 Co0.1 Ti3 O15 single-crystalline nanoplates were successfully synthesized by the hydrothermal method. The intrinsic multiferroic property was verified by electron holography and piezoresponse force microscopy in a single nanoplate. Abstract : In recent years, much attention has been paid to layer-structured Bi4 Bi m −3 Fe m −3− x M x Ti3 O3 m +3 (BFMTO, M = Co, Mn) compounds due to their potential as high temperature single phase multiferroic materials. However, BFMTO single crystals have been rarely reported in the past, though they are better candidates for studying the corresponding intrinsic multiferroics as well as the platform for making future devices, due to their structural complexity and difficulties in fabrication. In this article, Bi5 Fe0.9 Co0.1 Ti3 O15 single-crystalline nanoplates were synthesized by the hydrothermal method. The ferromagnetic domain structure of the nanoplate was investigated by electron holography. Denser phase contours were observed and the closed magnetic flux lines indicated a significant magnetic interaction between the neighboring nanoplates, which proved the ferromagnetic nature of the sample. Furthermore, M – H loops of the sample were also measured, in which the ferromagnetic Curie temperature reached ∼730.2 K. Besides, ferroelectric domains were also detected by using a piezoresponse force microscope. All the above-mentioned results indicate the first verification of the room temperature (RT) multiferroic behaviour in such single crystals, which will be useful for both future devices and understanding the underlining physics.